Gamma radiation and corn starch for conservation of cabbage leaves on post-harvest - Sanches, Alex Guimarães; Silva, Maryelle Barros da; Moreira, Elaine Gleice Silva; Costa, Jaqueline Macedo; Cordeiro, Carlos Alberto Martins (Scientia Agraria Paranaensis, 2017)
<span style="font-size: 10pt; font-family: ’Helvetica’,sans-serif; mso-fareast-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: ’Times New Roman’;" lang="EN-US">Due to the high perishability of cabbage leaves after harvest, the present work has the objective of evaluating the isolated and combined effect of different conservation techniques on cabbage shelflife. The experimental design was a 4 x 9 factorial arrangement with five replicates. The physico-chemical and sensorial components were evaluated every two days on the chlorophyll content, POD and PPO enzyme activity, soluble solids, pH, titratable acidity, loss of fresh mass, wilting, flavor and general quality. According to the results, a significant interaction was observed in all parameters evaluated. The use of corn starch (T3) in the isolated form presented similar results to the control (T1) in the same way as the combined effect of maize starch and gamma radiation did not differ when compared to the isolated effect of gamma radiation. The isolated effect of gamma radiation on all evaluated characteristics presented the best results, mainly in terms of soluble solids content, titratable acidity, chlorophyll content and taste.